Gambaran Pengetahuan Orang Tua tentang Kesehatan Gigi dan Mulut Anak di Masa Pandemi Covid-19 (Kajian pada TK Orchid Ciangsana) - Vevian Navlyn Ramadhany; Sri Ratna Laksmiastuti; Arianne Dwimega (Jurnal Kedokteran Gigi Terpadu, 2021)
Background : Oral health is an essential component of general health. Mother is an important figure for children's character building, providing support and role model to children, influencing children’s oral health. Parents’ knowledge about oral health, especially mothers, will affect children’s oral health. Many studies have reported there is a relationship between children’s oral health behavior, and their mother’s knowledge and oral health behavior. Aim: To assess parents’ knowledge about children’s oral health during the Covid-19 pandemic in Orchid Kindergarten Methods: A descriptive observational study with a cross-sectional design was conducted on 36 persons. The data were obtained using google form questionnaire and presented in the form of frequency distribution tables. The reliability and validity test is based on Cronbach’s Alpha and correlation’s coefficient value. Results: 30 respondents (93.75%) have a good level of knowledge and 2 respondents (6.25%) have a sufficient level of knowledge. Conclusion: The level of knowledge of parent in Orchid Kindergarten were categorized as good.